Структурно-прагматичні особливості мови газет - Рогач, Юлія; Rohach, Yulia (Східноєвропейський національний університет імені Лесі Українки, 2015)
Структурно-прагматичний аналіз мови сучасних австралійських газет здійснено через призму структурних особливостей побудови власне газетного тексту, ролі та місця заголовка. Досліджено лексичні, фразеологічні та синтаксичні особливості побудови різножанрових газетних повідомлень. Особливу увагу звернуто на мультимодальність – використання одиниць різних знакових систем на рівні цілого видання, окремої рубрики чи публікації, рекламних текстів та їхніх заголовків. Звернуто увагу на такі диференційні ознаки мови газет, як використання форм простого теперішнього часу замість минулого, лексичних скорочень, еліптичних речень, форм інфінітиву замість майбутнього часу, інверсіії тощо. Характерним для мови газет є використання великої кількості посилань на імена та назви, оскільки це надає більшої конкретики повідомленням. У той же час такий прийом вимагає від читачів певного рівня фонових знань. Особливий акцент зроблено на аналізі структурних особливостей та маніпулятивно-прагматичних потенцій заголовків. Заголовок виконує важливі завдання уже на першому етапі ознайомлення читача з текстом – притягнути його увагу і викликати зацікавлення. Це стає можливим через втілення виразної, номінативної та рекламної функцій, які реалізуються графічно. Крім того, важлива роль заголовка полягає в тому, щоб спонукати до прочитання тексту публікації, що реалізується через інформативну функцію, адже саме у заголовку сконденсовано її зміст і сенс. Оскільки сучасні газетні тексти відзначаються поліфонічністю, гібридністю та складністю композиції, то і сучасний заголовок наділений смисловою об’ємністю та комунікативно-функційною багатозначністю. З точки зору прагматики газетні заголовки характеризуються зовнішньою спрямованістю. У сучасній пресі вплив на читача, його емоційну та інтелектуальну сферу – це основне завдання заголовка, тому кожен заголовок несе не просто інформацію, а передає ставлення автора до змісту статті, повідомлення чи реклами, а також до фактів, викладених у них. This article is devoted to the structural pragmatic analysis of the language of modern Australian newspapers which is conducted from on the basis of the structural composition of a newspaper text, and the role and place of a headline in it. Lexical, phraseological and syntactic peculiarities of the structure of the newspaper texts of different genres were taken into account as well. A special attention has been paid to such inseparable component of the language of modern newspapers as multimodality, which is the usage of units of various sign systems on the level of a newspaper, in a separate column or article, advertisements and their headlines. Such distinctive features of the language of newspapers as the usage of the Simple Present tense of the verb instead of the Simple Past, infinitive instead of the Future Tense, lexical abbreviations and shortenings, elliptical sentences, inversion were pointed out. It was found out that it is typical for the language of newspapers to have many references to the authorities, well-known people and places because such references make the newspaper articles more precise and accurate. At the same time this method requires from the readers a certain level of background knowledge. A special accent has been made on the analysis of the structural peculiarities and manipulative pragmatic potentials of headlines. A headline performs very important tasks at the very first stage when a reader looks at the newspaper – it draws his attention and makes him interested in the material. It becomes possible thanks to the realization of the expressive, nominative and advertising functions that are implemented graphically. Besides this, a very important role of a headline is to make a reader read a newspaper text. This role is realized through an informative function as it is in the headline where the content of a newspaper text and its sense are condensed. As modern newspaper texts are characterized by polyphony, hybridity and a composition complexity, a modern headline is semantically deep and communicatively and functionally polysemantic. From the point of view of pragmatics, newspapers’ headlines are externally focused. In modern mass media an influence on a person, his emotional and intellectual spheres are considered to be the main tasks of a headline, that is why every headline does not only convey a piece of information but is shows an attitude of the author towards the content of an article, information or advertisement and towards the facts given in them.
Structural Pragmatic Peculiarities of the Language of Newspapers
Keywords: мова газет; структурно-прагматичні особливості газетного тексту; заголовок; мультимодальність; функційність; a language of newspapers; structural pragmatic peculiar features of a newspaper text; headline; multimodality; functions